Quantification of hafnium in selected inorganic and organometallic compounds - Malefo, Gontse Atlholang Adeline (University of the Free State, 2016)
The aim of this study was to develop a method for the dissolution and quantification of hafnium in hafnium containing compounds (which include the metal oxide, different inorganic compounds as well as a number of organometallic complexes). Various digestion techniques such as open vessel, flux fusion and microwave acid-assisted system were evaluated. The same time different reagents which include HNO3, HCl, H2SO4 alone and in combination with salts, e.g. (NH4)2SO4 + H2SO4 were evaluated while experimental conditions such as time and temperature were varied. Different analytical techniques such as inductively coupled plasma optical emission spectrometry (ICP-OES), infrared spectroscopy (IR), CHNS-micro analyses and X-ray crystallography were used for the quantification and characterisation of the synthesized hafnium compounds. The criteria used to select the Hf emission wavelength for ICPOES analysis was its sensitivity and the absence of spectral interferences from the acids used or the other elements present in solution. The experimental ICP-OES results obtained for the quantification of hafnium were also validated using different validation parameters which include accuracy, precision and the hypothesis test at a 95 % confidence interval to evaluate the validity of the most suitable digestion methods that were developed. Open vessels digestion of HfF4 using 98 % H2SO4 or 65 % HNO3 resulted in good hafnium recoveries which ranged from 97.8 – 99.9 % with relative standard deviation (RSD) within the range of 0.4302 – 0.4327 %. The hafnium content was also quantified in a number of newly synthesized hexafluorohafnate complexes as well as a thiocyanate complex. Hafnium recoveries ranged from 79(6) to 103(3) % for the sodium, potassium, rubidium, cesium, ammonium, methyl ammonium and tetraphenyl phosphine hexafluorohafnate complexes as well for the hafnyl thiocyanate complex. All the synthesised products were characterized with IR while the crystal structures of K2HfF6, Rb2HfF6, Cs2HfF6 and (PPh4)2HfF6.2H2O were successfully done with X-ray crystallography. Various digestion techniques such as open vessel, flux fusion and microwave acidassisted system with different mineral reagents which include HCl, 65 % HNO3 and aqua regia, 98 % H2SO4, a mixture of (NH4)2SO4 in 98 % H2SO4 and a mixture of NH4F and 98 % H2SO4 were investigated for the dissolution of hafnium oxide. Digestion by wet ashing yielded poor hafnium recoveries and ranged between 0.041(6) % and 3.82(1) %. Hafnium oxide was however successfully dissolved with flux fusion using Na2B4O7 followed by its dissolution with 98 % H2SO4. Hafnium recoveries improved from 72(4) to 100.8(7) %. Relatively poor hafnium recoveries ranging between 35(2) and 58(6) % (with time variation) were obtained using NaOH as flux and hafnium recoveries of 99(2) % were obtained using NH4HF2 as flux. Microwave acid-assisted digestion was also employed which improved the Hf recovery from 74.9(4) to 100(3) % with time and pressure as experimental variations. The method validation of the experimental results obtained for the quantification of hafnium using the hypothesis testing of at a 95 % confidence level was considered satisfactory. The experimentally obtained LOD values ranged from 0.0051 to 0.0985 and LOQs ranged between 0.051 to 0.9846 ppm in the different mineral acid used in this study. Other statistic parameters such as linearity and sensitivity were also investigated and gave satisfactory results.

Die doel van hierdie studie was om ‘n metode vir die susksesvolle vertering en kwantifisering van hafnium in hverskillende afnium bevattende verbindings (onder andere die metaaloksied, verskillende anorganiese verbindings asook organometaalkomplekse) te ontwikkel. Verskeie verteringstegnieke naamlik oophouer-, gesmelte-sout- en mikrogolfvertering is ondersoek. Tydens die studie van bogenoemde tegnieke is verskillende reagense soos HNO3, HCl, H2SO4 en mengsel van soute en sure soos byvoorbeeld (NH4)2SO4 + H2SO4 gebruik, terwyl die invloed van eksperimentele kondisies soos reaksietyd en temperatuur ook ondersoek is. Verskillende analitiese tegnieke wat insluit induktief-gekoppelde-optiese-plasma-emissie spektometrie (IGP-OES), infrarooi spektroskopie (IR), CHNS- mikro-element analises en Xstraalkristallografie is vir die kwantifisering en karakterisering van die verskillende hafnium bevattende verbindings gebruik. Die eksperimentele IGP-OES resultate wat vir die kwantifisering van hafnium verkry is, is ook met behulp van verskillende statistiese toeetse geëvalueer en die toets het onder andere akkuraatheid, presisie en die hipotese toets by ‘n 95 % betroubaarheidsgrens ingesluit. Hafniumherwinnings in HfCl4 en HfF4 wat strek tussen 97.8 – 99.9 % met ‘n standaardafwyling tussen 0.4302 – 0.4327 % in 98 % H2SO4 of 65 % HNO3 met behulp van oophouer-vertering is verkry. Die hafniuminhoud in ‘n aantal nuut-gesintetiseerde heksafluoro- en tiosianaathafnaat-komplekse (natrium, kalium, rubidium, sesium, ammonium, metielammonium en tetrafenielfosfonium) het tussen 79(6) en 103(3) % gewissel. Al die nuut-bereide produkte heksafluorokomplekse is met behulp van IR gekaraktiseer, terwyl kristalstrukture van K2HfF6, Rb2HfF6, Cs2HfF6 en (PPh4)2HfF6 susksesvol met behulp van X-straal kristallografie uitgevoer is.. Verskillende vereteringstegnieke wat insluit oophouer-, gesmelte-sout- en mikrogolfvertering is vir die vertering van hafniumokied geëvalueer. Bogenoemde tegnieke is in die teenwoordigheid van HCl, 65% HNO3 en aqua regia 98 % H2SO4, asook mengesels van NH4SO4 en 98 % H2SO4 en NH4F met 98 % H2SO4 bestudeer. Die ontbinding van HfO2 met die oophouervertering het swak herwinning opgelewer en het tussen 0.041(6) % en 3.82(1) % gestrek. Hafniumoksied is egter volledig met behulp van Na2B4O7 gesmelte-sout vertering (gevolg deur 98 % H2SO4 byvoeging) opgelos. Hf-herwinnings wat tussen 72(4) % en 100.8(7) % wissel is vir die verskillende gesmelte soute verkry. Relatiewe swak hafniumherwinning wat tussen 35(5) en 58(6) % strek (wisseling van reaksietyd), is vir NaOH as gesmelte sout gekry. Goeie hafniumherwinning van 99(2) % is verkry wanneer NH4HF2 as gesmelte soutmedium gebruik is. Mikrogolfvertering, in die teenwoordigheid van H2SO4, het hafniumherwinnings tussen 74.9(4) tot 100(3) % gelewer. Die validering van die eksperimentele resultate vir die vertering en kwantifisering van Hf is met behulp van die hipotese-toets (t-statistiese toets) by ‘n 95 % betroubaarheidsvlak uitgevoer. Die laagste vlakke waar Hf met sekerheid waargeneem is (LOD) het van 0.0051 tot 0.0985 gestrek terwyl die laagste vlakke waar Hf susksesvol gekwantifisser kan word (LOQ) het vanaf 0.051 tot 0.9846 dpm in verskillende mineraal-sure gestrek. Statistiese parameters soos lineariteit en sensitiwiteit is ook ondersoek en het bevredigende resultate gelewer.
Dissertation (M.Sc. (Chemistry))--University of the Free State, 2016
Keywords: Hafnium; Zirconium; Zircon; Baddeleyite; Quantification; Hafnium oxide; Inductively coupled optical emission spectroscopy (ICP-OES); Accuracy; Precision